The value of urine specimens in screening for male urethritis and its microbial aetiologies in Tanzania. Issue 6 (December 1992) - Mayaud, P; Changalucha, J; Grosskurth, H; Ka-Gina, G; Rugemalila, J; Nduba, J; Newell, J; Hayes, R; Mabey, D
Abstract : OBJECTIVE–To evaluate the first void urine (FVU) specimen in screening for urethritis and its microbial aetiologies in a male African population in which urinary schistosomiasis is also prevalent. PATIENTS AND METHODS–Two hundred and forty eight males aged 15-54 years provided FVU specimens: 55 patients from a clinic for sexually transmitted diseases (STD), 151 patients from a medical outpatient clinic and 42 villagers from an area of high endemicity for S haematobium. Specimens were tested for leucocyte esterase (LE) using a dipstick (Nephur-Test+Leuco, Boehringer-Mannheim France SA). Ova of S haematobium were sought in terminal urine samples from all subjects. For all STD patients, and all medical outpatients with a positive LE test, urine and urethral swabs were tested for Chlamydia trachomatis antigen, and urethral swabs were tested for Neisseria gonorrhoeae by gram stain and isolation. RESULTS–The prevalence of LE positivity was 38/41 in STD patients with urethral signs or symptoms (93%), 5/14 among other STD patients (36%), 21/151 among medical outpatients (15%) and 13/42 among villagers (31%). As a screening test for urethral infection (detection of gonorrhoea or chlamydia and/or > or = 5 polymorphs per high power field on gram stain) the LE test had a sensitivity of 94% and a specificity of 53% among STD patients. Of 24 STD patients with gonococcal or chlamydial infection, 23 had a positive LE test (96%). Among general medical outpatients, 12 of 22 with a positive LE test had either conventionally defined urethritis or gonococcal or chlamydial infection, giving a positive predictive value of 55% for the LE test in this group. Of 18 subjects in all groups with urinary schistosomiasis nine had a positive LE test (50%), although three of these also had gonorrhoea. Chlamydial antigen was detected in the FVU specimen of all six subjects in whom it was detected in a urethral swab, and in an additional three subjects in the outpatient group. CONCLUSIONS–The FVU, which is an easily collected and non-invasive specimen, can provide valuable information on the prevalence of urethritis and on its microbial aetiology among the general male population in African countries.